Social networks and academic achievement: peer-effects within Sao Paulo\'s public school system - Gukovas, Renata Mayer (2014)
Human beings are social animals, and the relevance of the networks an individual participates throughout his or her life has already been proved by several studies. In this dissertation, the social networks of 107 schools in São Paulo\'s public System are described intensively but not exhaustively. Several characteristics are detailed. Some of the characteristics observed go in the same direction as the common sense, while others go against it. Then, it is evaluated if the program \"TEM$+$Matemática\" has had an impact over the structure of friendship in some of these schools. This program consists of extra mathematics classes, and during its implementation, interested schools were randomized to participate, allowing this evaluation. It was observed that the schools that participated in the program had, in general, less cohesive networks, with fewer bonds and clusters. Among these schools students, the most affected were those who were eligible but did not show interest in participating on the classes. These students became less connected and less central in the networks. These results indicate that low performing students that do not show motivation suffer some sort of segregation.